2016
DOI: 10.1002/cbic.201500532
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Active‐Site Loop Conformations and Catalysis in Triosephosphate Isomerase: Insights from a Rare Variation at Residue 96 in the Plasmodial Enzyme

Abstract: Despite extensive research into triosephosphate isomerases (TIMs), there exists a gap in understanding of the remarkable conjunction between catalytic loop-6 (residues 166-176) movement and the conformational flip of Glu165 (catalytic base) upon substrate binding that primes the active site for efficient catalysis. The overwhelming occurrence of serine at position 96 (98% of the 6277 unique TIM sequences), spatially proximal to E165 and the loop-6 residues, raises questions about its role in catalysis. Notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…We also determined the kinetic constants for two of the extensively studied pathogenic mesophilic TIMs viz., Trypanosoma brucei TIM, TbTIM, (k cat = 945 s −1 ; K m = 0.17 mM) and Plasmodium falciparum TIM, PfTIM, (k cat = 500 s −1 ; K m = 0.9 mM) under the same assay conditions at 25 °C (Table 1). The PfTIM and TbTIM kinetic parameters were in agreement with previous studies [33,52]. Pairwise sequence alignment (ClustalOmega online server [53]) of the three protein sequences (SwissProt online database [54]) showed that the sequence identity between LiTIM-TbTIM is 35%, LiTIM-PfTIM is 40% and PfTIM-TbTIM is 42% out of which around 28% residues are identical between all the three, ( Figure S2).…”
Section: Such Loss Of Activity Upon Dilution Of Protein and Incubatiosupporting
confidence: 88%
“…We also determined the kinetic constants for two of the extensively studied pathogenic mesophilic TIMs viz., Trypanosoma brucei TIM, TbTIM, (k cat = 945 s −1 ; K m = 0.17 mM) and Plasmodium falciparum TIM, PfTIM, (k cat = 500 s −1 ; K m = 0.9 mM) under the same assay conditions at 25 °C (Table 1). The PfTIM and TbTIM kinetic parameters were in agreement with previous studies [33,52]. Pairwise sequence alignment (ClustalOmega online server [53]) of the three protein sequences (SwissProt online database [54]) showed that the sequence identity between LiTIM-TbTIM is 35%, LiTIM-PfTIM is 40% and PfTIM-TbTIM is 42% out of which around 28% residues are identical between all the three, ( Figure S2).…”
Section: Such Loss Of Activity Upon Dilution Of Protein and Incubatiosupporting
confidence: 88%
“…Finally, the importance of loop 6 flexibility to efficient catalysis can also be seen in mutational studies of rare variations of position 96 (proline in the wild-type) of the TIM from Plasmodium falciparum ( Pf TIM) [73], which is analogous to the proline at position 168 in Tbb TIM [34]. In both cases, it is clear that this residue plays an important role in modulating the conformational transition of loop 6, and, most critically, in positioning E165 ( y TIM numbering) in a catalytically competent position in the TIM active site (Figure 2).…”
Section: Computational Modeling Of the Role Of Ligand-gated Conformatmentioning
confidence: 99%
“…studied F96 ( 95 ) in Plasmodium falciparum PfTIM. Using crystallographic data of different mutants in this position (S, H, Y, A and W) they concluded that a change in the water network in the catalytic site is affecting the properties of the enzyme and that residue 96 is optimizing the position of the catalytic residue E165 ( 164 ) . The inhibiting effect of some dyes on the activity of PfTIM was tested; a direct interaction of some of them with F96 was shown, suggesting that the quite unique F96 ( 95 ) of PfTIM could be a good target for drug design .…”
Section: Effect Of Specific Residues At Selected Positionsmentioning
confidence: 99%